Impact of a High-Fat Meal and Sprinkled Administration on the Bioavailability and Pharmacokinetics of Viloxazine Extended-Release Capsules (QelbreeTM) in Healthy Adult Subjects - Wang, Zhao; Kosheleff, Alisa R; Adeojo, Lilian W; Odebo, Oyinkansola; Liranso, Tesfaye; Schwabe, Stefan; Nasser, Azmi (European journal of drug metabolism and pharmacokinetics, 2022)
Background and Objectives Viloxazine extended-release (viloxazine ER) capsules (Qelbree TM ) is a novel nonstimulant recently approved as a treatment for attention-deficit/hyperactivity disorder in children and adolescents. Here, we determined whether the pharmacokinetics of viloxazine are impacted by consuming the capsule contents sprinkled on applesauce rather than an intact capsule, and the effect of a high-fat meal on the pharmacokinetics of viloxazine ER. Methods This was a randomized, open-label, crossover, three-treatment, three-period study in healthy adults using orally administered single-dose viloxazine ER 200 mg capsules. Subjects consumed: (1) an intact capsule after a 10-h fast (control condition); (2) the capsule contents sprinkled on one tablespoon of applesauce; and (3) an intact capsule with a standard high-fat meal. Blood samples were collected for 48 h post-dosing. Relative bioavailability analyses were performed to assess the impact of each test condition against the control condition (intact capsule, fasting). The absence of an impact was indicated if the 90% confidence interval (CI) for the least-squares geometric mean ratio (LSGMR) of maximal concentration ( C max ), the area under the concentration–time curve from time 0 to the last measurable concentration time (AUC last ), and the area under the concentration–time curve from time 0 to infinity (AUC inf ) were within the predetermined no-difference limits of 80–125%. Results Out of 27 enrolled subjects, 25 were included in the pharmacokinetic analysis. The LSGMR (90% CI) for viloxazine ER sprinkled vs. intact were 90.10% (83.35–97.40) for C max , 93.71% (89.09–98.57) for AUC last , and 95.37% (89.80–101.28) for AUC inf . The LSGMR (90% CI) for viloxazine ER consumed in the fed state vs. fasting state were 90.86% (84.05–98.21) for C max , 89.68% (85.26–94.33) for AUC last , and 92.35% (86.96–98.07) for AUC inf . The 90% CIs of the LSGMRs were within the predetermined no-difference limits of 80–125%. Viloxazine ER was well tolerated, with most adverse events reported as mild. Conclusions These data suggest that viloxazine ER can be consumed sprinkled on applesauce or as intact capsules with or without meals without significantly changing its pharmacokinetics.